EFFECTIVENESS OF COMICS ON STUDENT LEARNING OUTCOMES - Ruqiah Ganda Putri Panjaitan; Kurnia Ningsih; Novi Novi (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2020)
This study aimed to determine the effectiveness of comics on students' learning outcomes. The research population is students of eight grades. This research is a quasi-experimental design with a nonequivalent control group design. The determination of the research sample used the intact group technique. The average of students' learning outcomes in the experimental class, which is using comic is 15.29 while the control class, which is using PowerPoint is 11.90, and the value of effect size is 1.56. The learning by using comics is sufficient to increase the students' learning outcomes.